The Impact Of E-Service Quality To Wards Customre Satisfaction On The User Of Internet Banking In PT. Bank Rakyat Indonesia Tbk (Persero) - Deni Ardiansyah; Lies Handrijaningsih (International Journal of Science, Technology & Management, 2021)
This research aims to analyze the impact of electronic service quality which consists of efficiency, fulfillment, reliability, privacy, responsiveness, contact, and compensation towards the customer satisfaction on the user of internet banking in PT Bank Rakyat Indonesia, Persero. Customer satisfaction is an urgent matter in banking and is one of the company duty to create that satisfaction out of every single service provided. The sample used in this research are respondents which are customers who use internet banking service from BRI. The data used in this research is primary data collected by conducting online questionnaires to 150 respondents. Analyzing technique used is validity, reliability, classical assumption, multiple linear regression, t, F, and the coefficient of determination test. The result shows that simultaneously, electronic service quality which consists of efficiency, fulfillment, reliability, privacy, responsiveness, contact, and compensation do have an impact towards customer satisfaction on the user of internet banking service of BRI. The finding on partial test shows that efficiency, fulfillment, contact and compensation has an impact towards customer satisfaction whereas reliability, privacy, and responsiveness do not.